NasiQu: Designing Mobile Applications with the Concept of Social Entrepreneurship for Hunger People Using Agile Methods - Hidayat, Hendra; Yulastri, Asmar; Susanto, Perengki; Ardi, Zadrian; Yustisia, Henny (JOIV : International Journal on Informatics Visualization, 2024)
Entrepreneurship is becoming an essential part of everyday life today. But the social problems of society, especially cases of hunger, have also become an essential issue to date. Digital entrepreneurship has become a trend recently, with many digital business platforms and emerging applications. However, combining digital entrepreneurship with social activities becomes more attractive, which we know as Digital Social Entrepreneurship. This study describes and explains the stages in designing NasiQu, a mobile social entrepreneurship application, to see how agile can make digital social entrepreneurship interesting by involving people's sense of concern for people in need, in this case, hungry people. The Agile method, one of many used in software development, is the one that is being used. The Agile method is a short-term system development approach that calls for quick adaptation and developers who can work with any change. The results of this product from NasiQu can facilitate donations in the form of packaged rice to those who need food; in the case of this implementation, it is still specifically for orphans. In this application, there are three users, namely donors, admins, and partners. All these users have different roles and application usage flows. In addition, this application makes food donation activities more effective and can be done anywhere and anytime. It is hoped that the ongoing implementation of this activity will help many people who need food and impact opening new job opportunities.